The Future of Recordkeeping: The Legal and Regulatory Considerations of Blockchain Adoption (Lead City International Journal of Library, Information & Communication Sciences, 2025)
This paper examines blockchain technology’s impact on the future of recordkeeping, particularly its ability to enhance transparency, security, and accountability across sectors such as supply chain management and healthcare. Blockchain’s distributed ledger technology (DLT) promises automated compliance through smart contracts, which can streamline operations and reduce administrative tasks. However, regulatory frameworks like General Data Protection Regulation GDPR introduce challenges, especially where blockchain’s immutability conflicts with data privacy requirements, such as the right to be forgotten. Legal considerations surrounding smart contracts, jurisdiction, and cross-border data storage further complicate blockchain’s adoption. This paper advocates for adaptive regulatory frameworks and cross-sector collaboration to reconcile blockchain’s strengths with compliance demands, ensuring its sustainable integration into recordkeeping practices.